Effects of extra virgin olive oil suplementation on BMI and HbA1C in female adolescent - Wenny Rahmawati; Dwi Norma Retnaningrum (Poltekkes Kemenkes Bandung, 2026)
Background: Diabetes among children and adolescents represents a significant health concern that is on the rise due to unhealthy lifestyle choices. According to the Indonesian Diabetes Association (IDAI), the incidence of diabetes in children increased by 70 times from 2010 to January 2023. EVOO is rich in bioactive compounds that may influence glucose metabolism and body composition. Objective: This study aimed to evaluate the impact of EVOO supplementation in adolescent girls. Methods: A quasi-experimental design with a control group was employed for this research. The population of this study was all female adolescents at SMKN 13 Malang, and subjects were selected through purposive sampling. The subjects consisted of 30 female adolescents divided into an intervention group (n=15) receiving 10 ml/day of EVOO supplementation for 3 months and a control group (n=15) receiving no treatment.The parameters assessed included body weight, height, BMI, and HbA1c levels, measured before and after the intervention. Data analysis was conducted using the t-test and Mann-Whitney U test. Results: The results indicated a significant reduction in body weight (from 61.00±4.93 kg to 59.73±4.54 kg; p=0.000), BMI (from 25.50±0.57 kg/m² to 24.94±0.74 kg/m²; p=0.000), and HbA1c levels (from 5.30±0.19% to 5.18±0.16%; p=0.001). Although height showed a slight increase, this change was not statistically significant (from 154.33±5.68 cm to 154.67±5.51 cm; p=0.150). The control group did not exhibit significant changes across any of the parameters. Conclusion: The administration of EVOO is effective in reducing body weight, BMI, and HbA1c levels in adolescent girls, while it does not impact height. Therefore, EVOO may serve as a valuable adjunctive therapy for weight management and glycemic control in adolescents.